Aggregation-induced CPL response from chiral binaphthyl-based AIE-active polymers via supramolecular self-assembled helical nanowires. (9th May 2018) - Ma, Jing; Wang, Yuxiang; Li, Xiaojing; Yang, Lan; Quan, Yiwu; Cheng, Yixiang
Abstract: In this paper chiral polymer R -P could be synthesized by click polymerization reaction of ( R )-3, 3′-diethynyl-2, 2′-bis(octyloxy)-1, 1′-binaphthalene ( R -M-1 ) and 1, 2-bis(4-azidophenyl)-1, 2-diphenylethene (M-2 ), and S -P was obtained by click polymerization reaction of ( S )-3, 3′-diethynyl-2, 2′-bis(octyloxy)-1, 1′-binaphthalene ( S -M-1 ) andM-2, respectively. R - /S -P enantiomers can show strong aggregation-induced circularly polarized luminescence (AICPL) emission signals in the aggregate and cast-spin film, and the dissymmetry factors ( g lum ) can be up to 6.97 × 10 −3 and 1.45 × 10 −2, respectively. The SEM images further demonstrate that AICPL response behavior of R - /S -P can be attributed to the formation of the supramolecular self-assembled helical nanowires in the aggregation state at 90% of the fraction of water ( f w ). Graphical abstract: Chiral conjugated polymer enantiomers incorporating 1, 1'-binaphythyl and tetraphenylethene (TPE) can exhibit strong CPL signals due to the formation of the supramolecular self-assembled helical nanowires in the aggregate.Image 1 Highlights: Two chiral conjugated polymer enantiomers R -P and S -P were designed and synthesized via click polymerization. The resulting polymers exhibit obvious AIE behavior. These two polymers can exhibit great CPL emission signals in the aggregates and cast-spin film.